Study of Religious Tourism at the Darussalam Belawa Mosque: Analysis of the Suitability of Cooper's 4A Aspects (Attraction, Amenity, Accessibility, Ancillary) in Destination Development - Elfrianto; Akbar, Muh.; Sultan, Muh. Iqbal (South Eastern European Journal of Public Health, 2025)
This research is a study of religious tourism at the Darussalam Belawa Mosque using a qualitative descriptive approach in analyzing the suitability of Cooper's 4A aspects (Attraction, Amenity, Accessibility, Ancillary). The aim of this research is to provide information regarding strategies for developing religious tourism objects and matters relating to supporting and inhibiting factors in the development of religious tourism objects at the Darussalam Belawa Mosque. The research results show that religious tourism in the Attraction aspect has fulfilled its status as a religious tourist attraction because it contains history and culture. This is what makes visitors interested in coming. However, the aspects of Amenity, Accessibility, Ancillary are not adequate so managers need management to develop so that religious tourism can fulfill these four aspects.